Book Review: Alexa Alice Joubin, Shakespeare and East Asia. New York, Oxford UP, 2021. xiii + 258 pp. ISBN: 978-0-19-870357-0. - Mohd Faiz, Muhammad Adib (SARE: Southeast Asian Review of English, 2023)
This book review analyses Alexa Alice Joubin’s Shakespeare and East Asia, a recent contribution to the field of Asian Shakespeares. In this sprawling work, Joubin analyses East Asian Shakespeare adaptations from the 1950s to the present day, showing how each displays a process of creative appropriation and subversion. In addition to reviewing the book’s contents, this review considers Joubin’s theoretical and interdisciplinary hybridity, showing how Joubin combines techniques to yield new insights. However, the review also considers the drawbacks of Joubin’s ambitious approach, which undermines the book’s argumentative coherence and leaves key research questions unexplored.